2002
DOI: 10.1002/nme.522
|View full text |Cite
|
Sign up to set email alerts
|

A multilevel genetic algorithm for the optimum design of structural control systems

Abstract: SUMMARYA multilevel genetic algorithm (MLGA) is proposed in this paper for solving the kind of optimization problems which are multilevel structures in nature and have features of mixed-discrete design variables, multi-modal and non-continuous objective functions, etc. Firstly, the formulation of the mixed-discrete multilevel optimization problems is presented. Secondly, the architecture and implementation of MLGA are described. Thirdly, the algorithm is applied to two multilevel optimization problems. The ÿrs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 18 publications
(18 reference statements)
0
10
0
Order By: Relevance
“…This shortcoming inspired researchers to explore using the relatively new and innovative evolutionarybased optimization techniques. For example, these methods have been used recently to address structural engineering optimization problems: Shuffled Complex Evolution Optimizer (SCEO), Ant Colony Optimization (ACO), the Genetic Algorithms (GA), and Particle Swarm Optimizer (PSO) (e.g., [16][17][18][19][20][21][22][23][24]). …”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
“…This shortcoming inspired researchers to explore using the relatively new and innovative evolutionarybased optimization techniques. For example, these methods have been used recently to address structural engineering optimization problems: Shuffled Complex Evolution Optimizer (SCEO), Ant Colony Optimization (ACO), the Genetic Algorithms (GA), and Particle Swarm Optimizer (PSO) (e.g., [16][17][18][19][20][21][22][23][24]). …”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
“…Genetic algorithms (GA) have also been implied to solve problems regarding topology optimization [5,12,[24][25][26][27]. The genetic algorithm is based on the evolutionary method of natural selection, survival of the fittest, and adaption.…”
Section: Structural Optimizationmentioning
confidence: 99%
“…It was showed that GA can probably converge to global optimality [14][15][16][17]. The principles of GA are individual intercompetition and survival-of-the-fittest in population.…”
Section: Introduction Of Gesomentioning
confidence: 99%
“…The GA search is based on the principles of "survival-of-thefittest" and adaptation. Structural optimizations and parameter determinations are two essential applications of GA [14][15][16][17][18]. In this paper, the performance of ESO is improved significantly by introducing the concept of probability and survival-of-thefittest of GA to ESO to develop a new method called Genetic Evolutionary Structural Optimization (GESO).…”
Section: Introductionmentioning
confidence: 99%